Integration of MicroRNAs with nanomedicine: tumor targeting and therapeutic approaches - Telkoparan-Akillilar, Pelin; Chichiarelli, Silvia; Tucci, Paolo; Saso, Luciano (Frontiers in Cell and Developmental Biology, 2025)
MicroRNAs (miRNAs) are small, non-coding RNA molecules that play a pivotal role in the post-transcriptional regulation of gene expression. Over the past decade, they have emerged as key regulators in cancer progression, influencing different cellular processes such as proliferation, apoptosis, metastasis, and immune evasion. Their unique ability to target multiple genes simultaneously makes miRNAs highly attractive as potential therapeutic agents in oncology. However, several challenges have hindered their direct clinical application, most notably their inherent instability in biological fluids, rapid degradation by nucleases, and inefficient delivery to specific tumor sites. Additionally, off-target effects and the potential for toxicity further complicate the therapeutic use of miRNAs. Nanomedicine offers a promising solution to these challenges by enabling the development of advanced platforms for the stable, safe, and targeted delivery of miRNAs. Nanoparticle-based delivery systems, such as liposomes, polymeric nanoparticles, and inorganic nanocarriers, can protect miRNAs from degradation, improve their bioavailability, and allow for precise tumor targeting through passive or active targeting mechanisms. These nanocarriers can also be engineered to release miRNAs in response to specific stimuli within the tumor microenvironment, enhancing therapeutic efficacy while minimizing side effects. This review will explore the integration of miRNAs with nanotechnology, focusing on various nanoparticle formulations and their roles in enhancing miRNA stability, specificity, and function in cancer treatment. In addition, we will discuss current advances in preclinical and clinical applications, highlight promising tumor-targeting strategies, and address the remaining challenges such as toxicity, immunogenicity, and scalability. Future research should focus on overcoming these barriers, ultimately paving the way for the widespread adoption of personalized miRNA-based nanomedicine in cancer therapy.